Exercise and education versus saline injections for knee osteoarthritis: a randomised controlled equivalence trial. Issue 4 (29th November 2021) - Bandak, Elisabeth; Christensen, Robin; Overgaard, Anders; Kristensen, Lars Erik; Ellegaard, Karen; Guldberg-Møller, Jørgen; Bartholdy, Cecilie; Hunter, David J; Altman, Roy; Bliddal, Henning; Henriksen, Marius
Abstract : Objective: To compare the efficacy of an exercise and education programme with open-label placebo given as intra-articular injections of inert saline on pain and function in individuals with knee osteoarthritis (OA). Methods: In this open-label, randomised controlled trial, we recruited adults aged ≥50 years with symptomatic and radiographically confirmed knee OA in Denmark. Participants were randomised 1:1 to undergo an 8-week exercise and education programme or four intra-articular saline injections over 8 weeks. Primary outcome was change from baseline to week 9 in the Knee Injury and Osteoarthritis Outcome Score (KOOS) questionnaire pain subscale (range 0 (worst)–100 (best)). Prespecified equivalence margins of ±8 KOOS pain points were chosen for the demonstration of comparable efficacy. Key secondary outcomes were the KOOS function and quality of life subscales, and patients' global assessment of disease impact. Results: 206 adults were randomly assigned: 102 to exercise and education and 104 to intra-articular saline injections. For the primary outcome, the least squares mean changes in KOOS pain were 10.0 for exercise and education and 7.3 for saline injections (difference 2.7 points, 95% CI −0.6 to 6.0; test for equivalence p=0.0008). All group differences in the key secondary outcomes respected the predefined equivalence margins. Adverse events and serious adverse events were similar in the two groups. Conclusion: In individuals with knee OA, an 8-week exercise and education programme provided efficacy for symptomatic and functional improvements equivalent to that of four open-label intra-articular saline injections over 8 weeks. Trial registration number: NCT03843931 .